PEMEC five-in-one electrode and preparation method thereof

By using the PEMEC five-in-one electrode method in the preparation of membrane electrodes, the hot pressing composite technology of titanium mesh electroplating layer and nano-scale catalysts is solved, and high-performance and low-cost films are achieved Electrode preparation.

CN119243203AActive Publication Date: 2025-01-03TSINGHUA UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411268697.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2025-01-03
Estimated Expiration
2044-09-11

AI Technical Summary

Technical Problem

During the preparation process of traditional membrane electrodes, precious metal catalysts are easily wasted, and leakage of the porous transport layer causes uneven distribution of the catalysts, affecting the electrode performance and cost.

Method used

Using PEMEC five-in-one electrode preparation method, the catalytic layer skeleton is formed by electroplating metal on the titanium mesh, the catalytic layer ink is prepared using nano-scale iridium oxide and carbon-backed platinum catalyst, and the catalytic layer is formed by ultrasonic spraying, and the catalytic layer is covered with Nafion solution. The hot pressing compound is used to form a five-in-one electrode, avoiding waste of precious metals and increasing catalyst adhesion.

Benefits of technology

It effectively reduces the waste of precious metals, improves the performance of the electrode and the water and gas transmission effect, reduces the manufacturing cost of the electrode, and improves the utilization rate of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243203A_ABST
    Figure CN119243203A_ABST
Patent Text Reader

Abstract

The invention provides a PEMEC five-in-one electrode and a preparation method of the PEMEC five-in-one electrode. The method comprises the following steps: performing metal electroplating treatment on a titanium mesh to obtain a catalyst layer framework; preparing anode catalyst layer ink and cathode catalyst layer ink; printing ink is sprayed to one side of the catalyst layer framework through ultrasonic spraying, and an anode catalyst layer and a cathode catalyst layer are formed respectively; covering the surface of the catalyst layer with a Nafion solution to form a Nafion layer; standing and molding to obtain a negative electrode and a positive electrode; and respectively compounding the negative electrode and the positive electrode to the two sides of the proton exchange membrane subjected to hot pressing treatment through hot pressing to obtain the PEMEC five-in-one electrode. According to the preparation method, the PTE electrode is prepared by taking the titanium mesh as a framework in a non-uniform loading manner, and the five-in-one electrode is obtained by combining a proton exchange membrane, so that the problem of waste of noble metal can be solved, and the prepared electrode can be applied to a PEM electrolytic bath and can also be applied to reaction devices with the same structure, such as a PEM fuel cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrogen energy, and in particular relates to a PEMEC five-in-one electrode and a preparation method thereof. Background Art

[0002] Traditional commercial membrane electrodes are usually in the form of CCM (the catalytic layer is coated on the proton exchange membrane), which is then combined with a porous transport layer, a bipolar plate and other components to form an electrolyzer. In this way, the catalytic layer that is not in direct contact with the porous transport layer will be wasted due to ohmic impedance.

[0003] In order to solve the problem of precious metal waste, many studies have begun to prepare PTE methods, but most studies still use titanium felt as a porous transport layer. This will cause leakage when spraying the catalytic layer ink. The ink that leaks into the titanium felt will produce an "island" effect, which not only causes catalyst waste, but also affects the water vapor transmission of the electrode. Therefore, the traditional titanium felt preparation of PTE cannot reduce the manufacturing cost of membrane electrodes. Summary of the invention

[0004] In order to solve the above technical problems, the purpose of the present invention is to provide a PEMEC five-in-one electrode and a preparation method thereof, which can avoid the waste of precious metals in the PEMEC electrode and reduce the manufacturing cost of the electrode.

[0005] To achieve the above object, the present invention first provides a method for preparing a PEMEC five-in-one electrode, which comprises the following steps:

[0006] Electroplating the titanium mesh with metal to form an electroplating layer to obtain a catalytic layer skeleton;

[0007] Prepare an anode catalyst layer ink and a cathode catalyst layer ink, wherein the anode catalyst layer ink is made of a nano-scale iridium oxide catalyst, a Nafion solution, deionized water, and a solvent (preferably n-propanol), wherein the mass ratio of the polymer material in the Nafion solution to the nano-scale iridium oxide catalyst is (0.125-0.5):1, and the solid content of the anode catalyst layer ink is 1%-5%; the cathode catalyst layer ink is made of a nano-scale carbon-supported platinum catalyst, a Nafion solution, deionized water, and a solvent, wherein the mass ratio of the polymer material in the Nafion solution to the carbon carrier of the nano-scale carbon-supported platinum catalyst is (0.35-1):1, and the solid content of the cathode catalyst layer ink is 1%-2%;

[0008] The anode catalyst layer ink and the cathode catalyst layer ink are respectively sprayed onto one side of the catalyst layer skeleton by ultrasonic spraying to form the anode catalyst layer and the cathode catalyst layer respectively;

[0009] Covering the surface of the anode catalyst layer and the surface of the cathode catalyst layer with Nafion solution respectively to form a Nafion layer, thereby obtaining a cathode electrode and an anode electrode;

[0010] The cathode electrode and the anode electrode are respectively hot-pressed with the catalyst layer and the Nafion layer facing upward, the hot-pressing temperature includes but is not limited to 110° C.-150° C., and the hot-pressing pressure includes but is not limited to 4 MPa-12 MPa, to obtain a cathode electrode and an anode electrode, respectively;

[0011] The cathode electrode and the anode electrode are respectively heat-pressed and composited to the two sides of the proton exchange membrane that has been heat-pressed to obtain the PEMEC five-in-one electrode.

[0012] In the above preparation method, preferably, the mass ratio of the polymer material in the Nafion solution to the carbon carrier of the nanoscale carbon-supported platinum catalyst is (0.6-1):1.

[0013] In the above preparation method, the nano-scale iridium oxide catalyst is nano-scale iridium oxide particles.

[0014] In the above preparation method, the mass ratio of deionized water to solvent in the anode catalyst layer ink can be adjusted according to actual needs, preferably (0.5-1):50; the mass ratio of deionized water to solvent in the cathode catalyst layer ink can be adjusted according to actual needs, preferably (5-10):50.

[0015] In the above preparation method, preferably, the titanium mesh is a TA1 titanium mesh (American standard GR1 type); more preferably, the titanium mesh is a plain or twill weave with a pore size of 50-600 mesh (more preferably 200 mesh). The titanium mesh with a plain or twill weave can bring better water vapor transmission effect (thickness is 200 μm) and uniformity.

[0016] In the above preparation method, preferably, the metal used for electroplating the titanium mesh is selected from one or a combination of two or more metals such as platinum, gold, iridium, etc. Electroplating these metals can improve the conductivity and reduce the contact impedance.

[0017] In the above preparation method, the thickness of the electroplating layer can be controlled according to the conventional method in the art as needed, and is preferably 500 nm.

[0018] In the above preparation method, preferably, the anode catalyst layer ink is prepared by the following steps: mixing nano-sized iridium oxide particles and deionized water, and dispersing them by water bath ultrasonic stirring to obtain a dispersion; sequentially adding Nafion solution (such as Dupont Nafion D520 solution, 5% concentration) and solvent (preferably n-propanol) to the above dispersion, ball milling to obtain a mixed solution; degassing the mixed solution to obtain the anode catalyst layer ink. The present invention firstly conducts separate water bath ultrasonic stirring on the deionized water and the noble metal catalyst (particles), and then adds the Nafion solution and solvent, which can prevent the noble metal from catching fire when encountering a low boiling point solvent.

[0019] In the above preparation method, preferably, the cathode catalyst layer ink is prepared by the following steps: mixing a nanoscale carbon-supported platinum catalyst and deionized water, and dispersing them by ultrasonic stirring in a water bath to obtain a dispersion; sequentially adding a Nafion solution and a solvent (preferably n-propanol) to the above dispersion, and ball milling to obtain a mixed solution; and degassing the mixed solution to obtain an anode catalyst layer ink.

[0020] In the above preparation method, preferably, the temperature when the nano-sized iridium oxide particles and deionized water are mixed is room temperature 25°C.

[0021] In the above preparation method, preferably, the particle size of the nano-scale iridium oxide particles is 2-20 nm.

[0022] In the above preparation method, the particle size of the carbon-supported platinum particles is mainly determined by the carbon carrier, and the carbon particles are preferably in the range of 40-60 nm.

[0023] In the above preparation method, preferably, the temperature when the nano-carbon-supported platinum catalyst and deionized water are mixed is room temperature 25°C.

[0024] In the above preparation method, preferably, the water bath ultrasonic stirring time is 3-5 minutes. The water bath ultrasonic stirring can fully mix the water and the catalyst and isolate the catalyst from air.

[0025] In the above preparation method, preferably, the ball milling adopts a planetary ball milling method, with a rotation speed of 300-1500 r / min and a time of 0.5-3 hours. Generally, 300 r / min corresponds to 3 hours and 1500 r / min corresponds to 30 minutes.

[0026] In the above preparation method, preferably, the degassing (defoaming) is carried out by centrifugal degassing, the centrifugal speed is 2000-2200r / min, and the time is 15-20 seconds. During the degassing process, the centrifugal speed should be controlled within the above range. If the speed is too low, the bubbles cannot be completely eliminated; if the speed is too high, the solids will sink to the bottom; both of these situations are not good for the ink.

[0027] In the above preparation method, preferably, the process of preparing the anode catalyst layer ink and the cathode catalyst layer ink respectively comprises the following steps:

[0028] The mixed liquid is dispersed by ultrasonic stirring to obtain a further dispersed mixed liquid, and then the further dispersed mixed liquid is degassed.

[0029] In the above preparation method, preferably, the dispersion frequency of the ultrasonic stirring dispersion is 5 seconds for dispersion and 3 seconds for rest.

[0030] In the above preparation method, preferably, the ultrasonic frequency of the ultrasonic stirring and dispersing is 20-40 kHz.

[0031] In the above preparation method, preferably, the ultrasonic stirring and dispersing time is 10-15 minutes.

[0032] In the above preparation method, preferably, the ultrasonic frequency of the ultrasonic spraying nozzle is 25-180 kHz, more preferably 120 kHz.

[0033] In the above preparation method, preferably, the thickness of the anode catalyst layer is 0.8-2 μm; the thickness of the cathode catalyst layer is 6-10 μm.

[0034] In the above preparation method, preferably, the thickness of the Nafion layer is 0.5-1 μm.

[0035] In the above preparation method, preferably, the proton exchange membrane subjected to hot pressing is obtained by hot pressing the proton exchange membrane under the conditions of temperature 100-120°C and pressure 8-12MPa (more preferably 110°C and 10MPa). Hot pressing the membrane can remove moisture and bubbles in the membrane, and the temperature needs to be greater than 100°C but not more than 120°C. Too high temperature and pressure will damage the membrane.

[0036] In the above preparation method, preferably, the temperature of the static molding is 130° C. and the time is 10 minutes.

[0037] In the above preparation method, preferably, the temperature of the hot pressing composite is 110-130°C (preferably 130°C), and the pressure is 2-5MPa (preferably 4-5MPa); the time of the hot pressing composite can be adjusted according to actual conditions, for example, the time is 5 minutes.

[0038] The present invention also provides a PEMEC five-in-one electrode, which is prepared by the above-mentioned preparation method.

[0039] According to a specific embodiment of the present invention, preferably, the above-mentioned PEMEC five-in-one electrode is composed of an anode catalyst layer, an anode catalyst layer skeleton, a proton exchange membrane, a cathode catalyst layer skeleton, and a cathode catalyst layer, and the surface of the anode catalyst layer and the surface of the cathode catalyst layer are respectively coated with a Nafion layer. Among them, the anode catalyst layer and the anode catalyst layer skeleton are combined into an anode electrode, which is located on the anode side of the proton exchange membrane; the cathode catalyst layer skeleton and the cathode catalyst layer are located on the cathode side of the proton exchange membrane; the anode catalyst layer skeleton and the cathode catalyst layer skeleton are respectively composed of titanium mesh, the anode catalyst layer is composed of nano-scale iridium oxide particles and Nafion polymer ionomers, and the cathode catalyst layer is composed of nano-scale carbon-supported platinum particles and Nafion polymer ionomers.

[0040] The technical solution of the present invention can be applied to different types of catalysts and proton exchange membrane materials. The catalyst ink is attached to the catalyst layer skeleton by ultrasonic spraying to form a non-uniformly loaded catalyst layer, thereby reducing the waste of catalyst. Then, the Nafion binder is sprayed on the catalyst layer to improve the adhesion of the catalyst layer and prevent the catalyst layer from falling off. Finally, a five-in-one electrode is formed by integrated hot pressing, and the electrode has the characteristics of low impedance and high performance.

[0041] The present invention uses titanium mesh as a skeleton and adopts a non-uniform loading form to prepare a PTE electrode, and then combines it with a proton exchange membrane to obtain a five-in-one electrode, which can solve the problem of precious metal waste in PEMEC electrodes. The prepared electrode can be used in a PEM electrolyzer, and can also be applied to a reaction device with the same structure such as a PEM fuel cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is a scanning electron microscope image of the PTE electrode prepared in Example 1.

[0043] Figure 2 This is a scanning electron microscope image of the PTE electrode prepared in Comparative Example 1.

[0044] Figure 3 SEM images of electrodes prepared at different pressures.

[0045] Figure 4Schematic diagram of a uniformly loaded CCM-type membrane electrode and a schematic diagram of a PTE-type electrode prepared by the present invention.

[0046] Figure 5 The performance comparison results of the PTE electrode prepared in Example 2 and the traditional CCM electrode. DETAILED DESCRIPTION

[0047] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.

[0048] Example 1

[0049] This embodiment provides a PEMEC five-in-one electrode, which is prepared by the following method:

[0050] 1. Catalytic layer skeleton pretreatment: Use 200μm thick, 200 mesh TA1 titanium mesh as the anode catalyst layer skeleton and cathode catalyst layer skeleton, and perform platinum metal electroplating treatment with an electroplating thickness of 500nm;

[0051] 2. Proton exchange membrane pretreatment: The FUMA-FS-990-PK proton exchange membrane was subjected to hot pressing at a temperature of 110°C, a pressure of 10 MPa, and a hot pressing time of 3 minutes;

[0052] 3. Preparation of anode catalyst layer ink: ① Mix iridium oxide particles with a particle size of 2-20nm and deionized water at room temperature of 25℃, and disperse them by water bath ultrasonic stirring for 3 minutes to obtain a dispersion; ② Add DupontNafion D520 solution (polymer concentration 5%) and n-propanol to the above dispersion in turn, and perform planetary ball milling at 1500r / min for more than 30min to obtain a mixed solution; ③ After ball milling, the mixed solution is further dispersed for 10min with a 40kHz ultrasonic stirring rod, and the dispersion frequency is 5 seconds for dispersion and 3 seconds for rest; ④ The further dispersed mixed solution is placed in a high-speed 2000r / min centrifugal defoamer for degassing for 20 seconds to obtain an anode catalyst layer ink; wherein the mass ratio of iridium oxide particles, Dupont Nafion D520 solution, deionized water, and n-propanol is 1:2.5:0.8:50;

[0053] 4. Preparation of cathode catalyst layer ink: The preparation method is the same as that of anode catalyst layer ink, except that nano-scale carbon-supported platinum catalyst of model TKKTEC10E60TPM is used to replace nano-scale iridium oxide particles, wherein the mass ratio of nano-scale carbon-supported platinum catalyst, Dupont Nafion D520 solution, deionized water, and n-propanol is 1:7:7:50;

[0054] 5. The anode catalyst layer ink and cathode catalyst layer ink were respectively coated on one side of two 200-mesh titanium meshes by ultrasonic spraying. The iridium oxide loading of the anode was 0.7 mg / cm 2 , the platinum loading of the cathode is 0.25 mg / cm 2 , forming an anode catalyst layer and a cathode catalyst layer respectively;

[0055] 6. Use a spray pen to cover the surface of the anode catalyst layer and the cathode catalyst layer with Dupont Nafion D520 solution. The polymer loading is 0.1 mg / cm 2 , forming a Nafion layer to obtain a cathode electrode and an anode electrode;

[0056] 7. Place the cathode electrode and the anode electrode at 130°C with the catalyst layer and the Nafion layer facing upward for 10 minutes to obtain a negative electrode and a positive electrode respectively;

[0057] 8. Place the electrode under a scanning electron microscope and magnify it 200 times to observe and judge the spraying effect.

[0058] 9. At 130°C, hot press the cathode electrode and anode electrode onto both sides of the proton exchange membrane obtained in step 2 at a pressure of 5 MPa, thereby obtaining a PEMEC five-in-one electrode.

[0059] The PEMEC five-in-one electrode was installed into the electrolytic cell fixture for performance testing.

[0060] Comparative Example 1

[0061] This comparative example provides a PEMEC five-in-one electrode, which is prepared by the following method:

[0062] 1. Catalytic layer skeleton pretreatment: Use 200μm thick, 200 mesh TA1 titanium mesh as the anode catalyst layer skeleton and cathode catalyst layer skeleton, and perform platinum metal electroplating treatment with an electroplating thickness of 500nm;

[0063] 2. Proton exchange membrane pretreatment: The proton exchange membrane is subjected to hot pressing treatment at a temperature of 110°C, a pressure of 10 MPa, and a hot pressing time of 3 minutes;

[0064] 3. Preparation of anode catalyst layer ink: ① Mix nano-sized iridium oxide particles with a particle size of 2-20nm and deionized water at room temperature of 25°C, and disperse them by water bath ultrasonic stirring for 3 minutes to obtain a dispersion; ② Add Dupont Nafion D520 solution (polymer concentration 5%) and n-propanol solvent to the above dispersion in sequence, and perform planetary ball milling at 1500r / min for more than 30min to obtain a mixed solution; ③ Put the mixed solution into a high-speed 2000r / min centrifugal defoamer for degassing for 20 seconds to obtain an anode catalyst layer ink; wherein the mass ratio of iridium oxide particles, Dupont Nafion D520 solution, deionized water, and n-propanol is 1:2.5:0.8:50;

[0065] 4. Preparation of cathode catalyst layer ink: The preparation method is the same as that of anode catalyst layer ink, except that nano-scale carbon-supported platinum catalyst of model TKKTEC10E60TPM is used to replace nano-scale iridium oxide particles, wherein the ratio of nano-scale carbon-supported platinum catalyst, Dupont Nafion D520 solution, deionized water, and n-propanol is 1:7:7:50;

[0066] 5. The above-mentioned anode catalyst layer ink and cathode catalyst layer ink are respectively coated on one side of two 200-mesh titanium meshes by ultrasonic spraying, and the iridium oxide loading of the anode is 0.7 mg / cm 2 , the platinum loading of the cathode is 0.25 mg / cm 2 , forming an anode catalyst layer and a cathode catalyst layer respectively;

[0067] 6. Use a spray pen to cover the surface of the anode catalyst layer and the cathode catalyst layer with Dupont Nafion D520 solution. The polymer loading is 0.1 mg / cm 2 , forming a Nafion layer to obtain a cathode electrode and an anode electrode;

[0068] 7. Place the cathode electrode and the anode electrode at 130°C with the catalyst layer and the Nafion layer facing upward for 10 minutes to obtain a negative electrode and a positive electrode respectively;

[0069] 8. At 130°C, hot press the cathode electrode and anode electrode onto both sides of the proton exchange membrane obtained in step 2 at a pressure of 5 MPa, thereby obtaining a PEMEC five-in-one electrode.

[0070] The PEMEC five-in-one electrode was installed into the electrolytic cell fixture for performance testing.

[0071] Example 2

[0072] This embodiment provides a PEMEC five-in-one electrode, which is prepared by the following method:

[0073] 1. Catalytic layer skeleton pretreatment: Use 200μm thick, 200 mesh TA1 titanium mesh as the anode catalyst layer skeleton and cathode catalyst layer skeleton, and perform platinum metal electroplating treatment with an electroplating thickness of 500nm;

[0074] 2. Proton exchange membrane pretreatment: The FUMA-FS-990-PK proton exchange membrane was subjected to hot pressing treatment at a temperature of 110°C, a pressure of 10 MPa, and a hot pressing time of 3 minutes;

[0075] 3. Preparation of anode catalyst layer ink: ① Mix iridium oxide particles with a particle size of 2-20nm and deionized water at room temperature of 25℃, and disperse them by water bath ultrasonic stirring for 3 minutes to obtain a dispersion; ② Add DupontNafion D520 solution (polymer concentration 5%) and n-propanol to the above dispersion in turn, and perform planetary ball milling at 1500r / min for more than 30min to obtain a mixed solution; ③ After ball milling, the mixed solution is further dispersed for 10min with a 40kHz ultrasonic stirring rod, and the dispersion frequency is 5 seconds for dispersion and 3 seconds for rest; ④ The further dispersed mixed solution is placed in a high-speed 2000r / min centrifugal defoamer for degassing for 20 seconds to obtain an anode catalyst layer ink; wherein the mass ratio of iridium oxide particles, Dupont Nafion D520 solution, deionized water, and n-propanol is 1:2.5:0.8:50;

[0076] 4. Preparation of cathode catalyst layer ink: The preparation method is the same as that of anode catalyst layer ink, except that nano-scale carbon-supported platinum catalyst of model TKKTEC10E60TPM is used to replace nano-scale iridium oxide particles, wherein the mass ratio of nano-scale carbon-supported platinum catalyst, Dupont Nafion D520 solution, deionized water, and n-propanol is 1:7:7:50;

[0077] 5. The above-mentioned anode catalyst layer ink and cathode catalyst layer ink were respectively coated on one side of two 200-mesh titanium meshes (platinum-plated and non-platinum-plated) by ultrasonic spraying to prepare the anode iridium oxide loading of 0.5 mg / cm 2 , 0.3mg / cm 2 , the platinum loading of the cathode is 0.25 mg / cm 2 , forming an anode catalyst layer and a cathode catalyst layer respectively;

[0078] 6. Use a spray pen to cover the surface of the anode catalyst layer and the cathode catalyst layer with Dupont Nafion D520 solution. The polymer loading is 0.1 mg / cm 2 , forming a Nafion layer to obtain a cathode electrode and an anode electrode;

[0079] 7. Place the cathode electrode and the anode electrode at 130°C with the catalyst layer and the Nafion layer facing upward for 10 minutes to obtain a negative electrode and a positive electrode respectively;

[0080] 8. At 130°C, hot press the cathode electrode and anode electrode onto both sides of the proton exchange membrane obtained in step 2 at a pressure of 5 MPa, thereby obtaining a PEMEC five-in-one electrode.

[0081] The PEMEC five-in-one electrode was placed in the electrolyzer fixture for ohmic impedance testing and compared with commercial membrane electrodes, such as Figure 5 shown.

[0082] Example 3

[0083] This embodiment provides a PEMEC five-in-one electrode, which is prepared by the following method:

[0084] 1. Catalytic layer skeleton pretreatment: Use 200μm thick, 200 mesh TA1 titanium mesh as the anode catalyst layer skeleton and cathode catalyst layer skeleton, and perform platinum metal electroplating treatment with an electroplating thickness of 500nm;

[0085] 2. Proton exchange membrane pretreatment: The FUMA-FS-990-PK proton exchange membrane was subjected to hot pressing treatment at a temperature of 110°C, a pressure of 10 MPa, and a hot pressing time of 3 minutes;

[0086] 3. Preparation of anode catalyst layer ink: ① Mix iridium oxide particles with a particle size of 2-20nm and deionized water at room temperature of 25℃, and disperse them by water bath ultrasonic stirring for 3 minutes to obtain a dispersion; ② Add DupontNafion D520 solution (polymer concentration 5%) and n-propanol to the above dispersion in turn, and perform planetary ball milling at 1500r / min for more than 30min to obtain a mixed solution; ③ After ball milling, the mixed solution is further dispersed for 10min with a 40kHz ultrasonic stirring rod, and the dispersion frequency is 5 seconds for dispersion and 3 seconds for rest; ④ The further dispersed mixed solution is placed in a high-speed 2000r / min centrifugal defoamer for degassing for 20 seconds to obtain an anode catalyst layer ink; wherein the mass ratio of iridium oxide particles, Dupont Nafion D520 solution, deionized water, and n-propanol is 1:2.5:0.8:50;

[0087] 4. Preparation of cathode catalyst layer ink: The preparation method is the same as that of anode catalyst layer ink, except that nano-scale carbon-supported platinum catalyst of model TKKTEC10E60TPM is used to replace nano-scale iridium oxide particles, wherein the mass ratio of nano-scale carbon-supported platinum catalyst, Dupont Nafion D520 solution, deionized water, and n-propanol is 1:7:7:50;

[0088] 5. The above-mentioned anode catalyst layer ink and cathode catalyst layer ink are respectively coated on one side of two 200-mesh titanium meshes by ultrasonic spraying, and the iridium oxide loading of the anode is 0.7 mg / cm 2 , the platinum loading of the cathode is 0.25 mg / cm 2 , forming an anode catalyst layer and a cathode catalyst layer respectively;

[0089] 6. Use a spray pen to cover the surface of the anode catalyst layer and the cathode catalyst layer with Dupont Nafion D520 solution. The polymer loading is 0.1 mg / cm 2 , forming a Nafion layer to obtain a cathode electrode and an anode electrode;

[0090] 7. Place the cathode electrode and the anode electrode at 130°C with the catalyst layer and the Nafion layer facing upward for 10 minutes to obtain a negative electrode and a positive electrode respectively;

[0091] 8. At 110°C, hot press the cathode electrode and anode electrode onto both sides of the proton exchange membrane obtained in step 2 at a pressure of 2 MPa, thereby obtaining a PEMEC five-in-one electrode.

[0092] The five-in-one electrode was placed in the electrolytic cell fixture for performance testing. The performance of the PEMEC five-in-one electrode reached 2V@3.2A / cm 2 .

[0093] Comparative Example 2

[0094] This comparative example provides a PEMEC five-in-one electrode, which is prepared by the following method:

[0095] 1. Catalytic layer skeleton pretreatment: Use 200μm thick, 200 mesh TA1 titanium mesh as the anode catalyst layer skeleton and cathode catalyst layer skeleton, and perform platinum metal electroplating treatment with an electroplating thickness of 500nm;

[0096] 2. Proton exchange membrane pretreatment: The proton exchange membrane is subjected to hot pressing treatment at a temperature of 110°C, a pressure of 10 MPa, and a hot pressing time of 3 minutes;

[0097] 3. Preparation of anode catalyst layer ink: ① Mix iridium oxide particles with a particle size of 2-20nm and deionized water at room temperature of 25℃, and disperse them by water bath ultrasonic stirring for 3 minutes to obtain a dispersion; ② Add DupontNafion D520 solution (polymer concentration 5%) and n-propanol solvent to the above dispersion in turn, and perform planetary ball milling at 1500r / min for more than 30min to obtain a mixed solution; ③ After ball milling, the mixed solution is further dispersed for 10min with a 40kHz ultrasonic stirring rod, and the dispersion frequency is 5 seconds for dispersion and 3 seconds for rest; ④ The further dispersed mixed solution is placed in a high-speed 2000r / min centrifugal defoamer for degassing for 20 seconds to obtain an anode catalyst layer ink; wherein the mass ratio of iridium oxide particles, Dupont Nafion D520 solution, deionized water, and n-propanol is 1:2.5:0.8:50;

[0098] 4. Preparation of cathode catalyst layer ink: The preparation method is the same as that of anode catalyst layer ink, except that nano-scale carbon-supported platinum catalyst of model TKKTEC10E60TPM is used to replace nano-scale iridium oxide particles, wherein the mass ratio of nano-scale carbon-supported platinum catalyst, Dupont Nafion D520 solution, deionized water, and n-propanol is 1:7:7:50;

[0099] 5. The above-mentioned anode catalyst layer ink and cathode catalyst layer ink are respectively coated on one side of two 200-mesh titanium meshes by ultrasonic spraying, and the iridium oxide loading of the anode is 0.7 mg / cm 2 , the platinum loading of the cathode is 0.25 mg / cm 2 , forming an anode catalyst layer and a cathode catalyst layer respectively;

[0100] 6. Use a spray pen to cover the surface of the anode catalyst layer and the cathode catalyst layer with Dupont Nafion D520 solution. The polymer loading is 0.1 mg / cm 2 , forming a Nafion layer to obtain a cathode electrode and an anode electrode;

[0101] 7. Place the cathode electrode and the anode electrode at 130°C with the catalyst layer and the Nafion layer facing upward for 10 minutes to obtain a negative electrode and a positive electrode respectively;

[0102] 8. At 150°C, hot press the cathode electrode and anode electrode onto both sides of the proton exchange membrane obtained in step 2 at a pressure of 8 MPa, thereby obtaining a PEMEC five-in-one electrode.

[0103] The PEMEC five-in-one electrode was placed in the electrolyzer fixture for performance testing. Analysis showed that a pressure of 6MPa would pierce the membrane and cause the electrode to short-circuit.

[0104] Comparative Example 3

[0105] This comparative example provides a conventional CCM-configured water electrolysis hydrogen production membrane electrode, which is a proton exchange membrane with catalyst layers uniformly coated on both sides. It is specifically prepared by the following steps:

[0106] 1. Prepare anode catalyst slurry: The catalyst slurry is composed of IrO2 catalyst particles, 5% Nafion solution, pure water and n-propanol in a mass ratio of 1:2.5:0.8:50, and the catalyst particles are evenly dispersed in the slurry by combining ball milling and ultrasonic dispersion;

[0107] 2. Preparation of uniform anode catalyst layer: Spray the anode catalyst slurry onto the surface of the proton exchange membrane by ultrasonic spraying to form a uniform anode catalyst layer with a catalyst loading of 1 mg / cm 2 ;

[0108] 3. Preparation of cathode catalyst slurry: The specific preparation process is the same as that of anode catalyst slurry, except that carbon-supported platinum catalyst is used to replace IrO2 particles, wherein the mass ratio of carbon-supported platinum catalyst (Pt loading is 60wt%), 5% concentration Nafion solution, deionized water, and n-propanol is 1:7:7:50;

[0109] 4. Preparation of uniform cathode catalyst layer: The cathode catalyst slurry is sprayed on the other side of the proton exchange membrane by ultrasonic spraying to form a uniform cathode catalyst layer. The cathode catalyst loading is 0.2 mg / cm 2 .

[0110] Figure 1 This is a scanning electron microscope image of the PTE electrode prepared in Example 1. Figure 2 This is a scanning electron microscope image of the PTE electrode prepared in Comparative Example 1. Figure 1 and Figure 2 By comparison, it can be seen that: Comparative Example 1 lacks a step of ultrasonic dispersion, and ball milling of the slurry is not enough, and the particles are unevenly dispersed; Example 1 further disperses the mixed liquid with a 40kHz ultrasonic stirring rod after ball milling, which can make the catalyst ink more well dispersed, so that it can be more evenly distributed after spraying onto the titanium mesh, without problems such as flash and burrs.

[0111] Figure 3 The scanning electron microscope images of electrodes prepared under different pressures. Figure 3 It can be seen that: when the temperature is too high, the proton exchange membrane will deform; when the pressure is too high, according to the local enlarged view, it can be seen that the mesh has been embedded in the membrane, reducing the membrane thickness, which will reduce the durability of the membrane.

[0112] Figure 4Schematic diagram of a uniformly loaded CCM membrane electrode (a) and a schematic diagram of a PTE electrode prepared by the present invention (b). Figure 4 It can be seen that the catalyst utilization rate of CCM membrane electrode is lower than that of PTE electrode.

[0113] Figure 5 The performance comparison results of the PTE electrode prepared in Example 2 and the traditional CCM electrode are shown in Figure 2. 2 The corresponding iridium oxide loading of the anode without platinum plating is 0.3 mg / cm 2 Technical solution: PTE (platinum plating) - 0.3mg / cm 2 The corresponding platinum-plated, iridium oxide loading of the anode is 0.3 mg / cm 2 Technical solution: PTE-0.5mg / cm 2 The corresponding iridium oxide loading of the non-platinized anode is 0.5 mg / cm 2 Technical solution: PTE (platinum plating) - 0.5mg / cm 2 The corresponding platinum-plated, iridium oxide loading of the anode is 0.5 mg / cm 2 Technical solution: CCM-1mg / cm 2 Corresponding to the traditional CCM electrode in Example 3.

[0114] Depend on Figure 5 The results shown show that the PTE electrode of the present invention has lower ohmic impedance and higher current per unit mass of catalyst, so the PTE electrode has a more efficient catalyst utilization rate than the traditional CCM electrode. Therefore, under the same performance, the PTE electrode requires less catalyst.

Claims

1. A method for preparing a PEMEC five-in-one electrode, comprising the following steps: Electroplating the titanium mesh with metal to form an electroplating layer to obtain a catalytic layer skeleton; Anode catalyst layer ink and cathode catalyst layer ink are prepared, wherein the anode catalyst layer ink is made of nano-scale iridium oxide catalyst, Nafion solution, deionized water, and solvent, wherein the mass ratio of the polymer material in the Nafion solution to the nano-scale iridium oxide catalyst is (0.125-0.5):1, and the solid content of the anode catalyst layer ink is 1%-5%; the cathode catalyst layer ink is made of nano-scale carbon-supported platinum catalyst, Nafion solution, deionized water, and solvent, wherein the mass ratio of the polymer material in the Nafion solution to the carbon carrier of the nano-scale carbon-supported platinum catalyst is (0.35-1):1, and the solid content of the cathode catalyst layer ink is 1%-2%; The anode catalyst layer ink and the cathode catalyst layer ink are respectively sprayed onto one side of the catalyst layer skeleton by ultrasonic spraying to form the anode catalyst layer and the cathode catalyst layer respectively; Covering the surface of the anode catalyst layer and the surface of the cathode catalyst layer with Nafion solution respectively to form a Nafion layer, thereby obtaining a cathode electrode and an anode electrode; The cathode electrode and the anode electrode are respectively placed in a static state with the catalyst layer and the Nafion layer facing upward to obtain a negative electrode and a positive electrode respectively; The cathode electrode and the anode electrode are respectively heat-pressed and composited to the two sides of the proton exchange membrane that has been heat-pressed to obtain the PEMEC five-in-one electrode.

2. The preparation method according to claim 1, wherein The titanium mesh is a TA1 type titanium mesh; preferably, the titanium mesh is plain or twill woven, with a pore size of 50-600 meshes, preferably 200 meshes.

3. The preparation method according to claim 1, wherein The anode catalyst layer ink is prepared by the following steps: mixing nano-sized iridium oxide particles and deionized water, and dispersing them by ultrasonic stirring in a water bath to obtain a dispersion; sequentially adding Nafion solution and solvent to the dispersion, and ball milling to obtain a mixed solution; degassing the mixed solution to obtain the anode catalyst layer ink; preferably, the solvent is n-propanol; The cathode catalyst layer ink is prepared by the following steps: mixing a nano-scale carbon-supported platinum catalyst and deionized water, and dispersing them by ultrasonic stirring in a water bath to obtain a dispersion; sequentially adding a Nafion solution and a solvent to the above dispersion, and ball milling to obtain a mixed solution; degassing the mixed solution to obtain an anode catalyst layer ink; preferably, the solvent is n-propanol.

4. The preparation method according to claim 3, wherein The water bath ultrasonic stirring time is 3-5 minutes; The ball milling adopts a planetary ball milling method, with a rotation speed of 300-1500r / min and a time of 0.5-3 hours; The degassing is carried out by centrifugal degassing, the centrifugal speed is 2000-2200r / min, and the time is 15-20 seconds.

5. The preparation method according to claim 3, wherein: The process of preparing the anode catalyst layer ink and the cathode catalyst layer ink comprises the following steps respectively: Performing ultrasonic stirring and dispersion on the mixed solution to obtain a further dispersed mixed solution, and then performing a degassing treatment on the further dispersed mixed solution; Preferably, the dispersion frequency of the ultrasonic stirring dispersion is 5 seconds for dispersion and 3 seconds for rest; Preferably, the ultrasonic frequency of the ultrasonic stirring dispersion is 20-40kHz; Preferably, the ultrasonic stirring and dispersing time is 10-15 minutes.

6. The preparation method according to claim 1, wherein The ultrasonic spraying nozzle has an ultrasonic frequency of 25-180 kHz.

7. The preparation method according to claim 1, wherein The thickness of the anode catalyst layer is 0.8-2 μm; the thickness of the cathode catalyst layer is 6-10 μm; Preferably, the thickness of the electroplating layer is 500 nm; Preferably, the thickness of the Nafion layer is 0.5-1 μm.

8. The preparation method according to claim 1, wherein The hot-pressed proton exchange membrane is obtained by hot-pressing the proton exchange membrane under the conditions of a temperature of 100-120° C. and a pressure of 8-12 MPa.

9. The preparation method according to claim 1, wherein The temperature of the static molding is 130° C. and the time is 10 minutes; Preferably, the temperature of the hot pressing compound is 110-130° C. and the pressure is 2-5 MPa.

10. A PEMEC five-in-one electrode, prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Membrane electrode for solid polymer membrane electrolytic bath and preparation method of membrane electrode

    CN115341223A

  • Membrane electrode of proton exchange membrane electrolytic tank of gradient pore catalyst layer and preparation method of membrane electrode

    CN116053542A

  • PEM electrolytic cell membrane electrode and preparation method thereof

    CN117535710A

  • CCM membrane electrode, preparation method therefor and use thereof

    WO2022170717A1